(3eaGJjM GdCUhds - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s ((3eMeO gGTe Hf eMeO bGSes)
(3ChdgG (B:s
(3GdMeO ddg (B... (3eaGJjM GddZGJ , bGd Gddg JHGQc (B... (3heG CQSdfG ef QShd EdG HdSGf bheg , Gdbhd aj GdOdGdI eaJGM GNJda GdYdeGA aj Cf GddaX gd jOd Ydi eYfGg HGdPGJ Ch HhVY GdhGVY Ydi Gdbhdjf GdChd Cfg dG jOd Ydjg HGdPGJ (B...s
(3BNQgG (B:s
.. (3haj GdCMcGe GJabhG Ydi Cf fSN SfI hSff GdYHGOI dG jchf fSNG dJdc GdYHGOI cfSN (B.. (3GdQCS hGdhbha Ydi jejf GdEeGe aj GdUdGI GfJgi heG PcQhg LjO bO aQZJ(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\ 543s
(3EjVGM Gdecfhf (B2\ 520s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs